Hubungan Dukungan Sosial Orangtua dengan Kecemasan Menghadapi Ujian Masuk Universitas pada Siswa Sekolah Menengah Atas Tingkat Akhir dalam Situasi Covid-19 - Anastasia Putri; Maria Nugraheni M. Rahayu (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this research is to determine the relationship between parental social support and anxiety in facing the University entrance exam test for the 12th grade students of Senior High School. The participants of this research are the 12th grade students of Senior High School who are about to take the University entrance exam test with a total of 122 participants. The sampling technique used in this research is quota sampling. The measurement instrument used is cognitive anxiety scale developed by Cassady & Johnson to measure anxiety and parental social support scale created by Gunandar referring to Sarafino's theory to measure parental social support. This research was conducted online with questionnaires distributed via Google Form to the 12th grade students of Senior High School. The correlation test uses Pearson correlation technique with the help of IBM SPSS program for Windows version 20. The result generated from this research shows that the correlation coefficient (r) = -0.300 with the value of sig 0.000 (p<0.05). This means that there is a negative relationship between anxiety and parental social support for the 12th grade students of Senior High School. This also could mean the higher the parental social support obtained, the lower the anxiety become, and vice versa.